Emotional Culture as Sociological Concept: On Emotional Turn in Understanding of Modern Society - Olga Simonova (Culture e Studi del Sociale)
The sociology of emotions aspires to give a description of the emotional culture of modern societies (most notably western societies); the peculiarities of the said culture contribute to the surge of interest in emotions in knowledge and everyday life—the so called “emotional turn”. The author attempts to determine the outlines of “emotional culture” concept, show what constitutes the distinctive nature of the sociological understanding of the emotional culture, which could provide an increment of knowledge and critical re-evaluation of modern social realities. The modern studies in the field of the sociology of emotions allow to suggest that in the modern societies a neo-sentimentalist culture is forming as an unintended consequence of rationalization of all the aspects of society life, modern consumer culture, individualization, etc. The emotional culture of modernity is characterized by the combination of rational attitude to emotions and simultaneous special attention to feelings, specific expression of collective emotions, persistent search for authentic feelings. One of the striking manifestations of the emotional culture of modernity is a phenomenon of “emotional labour”, when the ability to control emotions is commercialized both in public and private sphere.